Implementasi Karakter Peduli Sosial dan Kerja Keras dalam Lembaga Swadaya Masyarakat (Studi Kasus LSM Taruna Siaga Bencana Kabupaten Ngawi) - Syaiful, Muhammad An Nur (2016)
This research aim to describe the implementation, challenges and solutions in the implementation of social care character and hard work on LSM Tagana in Ngawi district. This research data gathered through informants, places and events, as well as the documents. Data collection technique used observation method, interview, documentation. Analysis of data using interactive models that have multiple stages namely data collection, data reduction, and conclusion. Implementation of the social care character in the LSM Tagana in Ngawi district is treating others with courtesy well against members of Tagana and people affected by the disaster, act politely in the activities of disastered, respect for others in the citizens Tagana and disaster victims, familiarize well attitude with others, work with a sincere, perform activities disastered by working together, a sense of concern for the environment and social, love each other for people and the problems faced by calm. Implementation of the hard work character in LSM Tagana in Ngawi district is a high sense of responsibility, evaluation and reporting of any conduct disastered, create a schedule activities in accordance with the conditions of the field, and utilize existing resources. Constraints in the implementation of social care character in LSM Tagana Ngawi district are differences in the nature and character of each individual, differences social status that exist in an environment Tagana and selfishness that exist within self the citizens Tagana. Constraints in the implementation of the hard work character in LSM Tagana in Ngawi district are a discrepancy between planning and implementation, time constraints with limited human resources. Solution to the constraints in the implementation of social care character in LSM Tagana in Ngawi district are provide training, reproduce meeting with planting moral agenda, providing an understanding between members Tagana order to create harmony in difference, and remind each other between members Tagana and strengthen team performance. Solution to the constraints in the implementation of the hard work character in LSM Tagana in Ngawi district are attempted to equalize between planning and implementation, set back the time, reconfirm the schedule that has been made so as not to collide with a the busyness or other activities, and provide training and to multiply networking with other LSM.